Study on Some Quality and Morpho-Physiological Traits of Durum Wheat (Triticum durum L. Desf.) Genotypes - BALKAN, Alpay; BİLGİN, Oğuz and BAŞER, İsmet and BALABAN GÖÇMEN, Damla and ÖZCAN, Kamil (ISPEC Journal of Agricultural Sciences, 2023)
The study was carried out in the experimental field of the Department of Field Crops, Faculty of Agriculture, Tekirdağ Namık Kemal University in 2020-2021. In the study, totally 25 durum wheat genotypes (6 cultivars, 12 advanced lines, and 7 landraces) were used as experimental material. The experiment was conducted in a randomized complete block design with 3 replications. In the study, the grain quality and morpho-physiological traits such as canopy temperature, chlorophyll content, leaf area index, and plant height were investigated in some durum wheat genotypes. The canopy temperature ranged from 23.33-20.43 OC, chlorophyll content 52.53-43.17 SPAD, leaf area index 3.63-1.77, thousand-grain weight 34.67-41.83 g, protein content 14.23-16.33%, test weight 78.93-87.03 kg hl-1, semolina colour 14.88-15.63 and plant height 99.00-75.33 cm in investigated durum wheat genotypes. Hacımestan and Sorgül genotypes for canopy temperature, Atkı 2, NZFM 1 and NZFM 7 genotypes for chlorophyll content, Atkı 2, NZFM 4 and NZFM 1 genotypes for leaf area index, Kıbrıs 2 and Ionia 3 genotypes for plant height, NZFM 1, NZFM 7 and Devedişi 2 genotypes for thousand-grain weight, Atkı 2 and Hacımestan 2 genotypes for protein content, Japiga and Boğacak 2 genotypes for test weight and Japiga, Boğacak, Kızıltan 91 and NZFM 7 genotypes for semolina colour were determined as promising genotypes.